2001
DOI: 10.1038/nn746
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of ionotropic glutamate receptors in response to mGluR activation

Abstract: Activation of group 1 metabotropic glutamate receptors (mGluRs) stimulates dendritic protein synthesis and long-term synaptic depression (LTD), but it remains unclear how these effects are related. Here we provide evidence that a consequence of mGluR activation in the hippocampus is the rapid loss of both AMPA and NMDA receptors from synapses. Like mGluR-LTD, the stable expression of this change requires protein synthesis. These data suggest that expression of mGluR-LTD is at least partly postsynaptic, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
490
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(537 citation statements)
references
References 33 publications
41
490
3
3
Order By: Relevance
“…The G q -coupled mGlu5 is highly expressed at excitatory synapses in the CA1 hippocampal neurons (Lujan et al, 1996) and contributes to a number of postsynaptic functions in the central nervous system, such as increased neuronal excitability, intracellular Ca 21 increase, synaptic plasticity, and pain (Snyder et al, 2001;Ireland and Abraham, 2002;Gubellini et al, 2003;Rae and Irving, 2004). Homer proteins are known to link mGluRs to other postsynaptic density proteins (Shiraishi-Yamaguchi and Furuichi, 2007;Niswender and Conn, 2010) and play a vital role in coupling the receptors with downstream effectors (Mao et al, 2005;Jung et al, 2007;Won et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G q -coupled mGlu5 is highly expressed at excitatory synapses in the CA1 hippocampal neurons (Lujan et al, 1996) and contributes to a number of postsynaptic functions in the central nervous system, such as increased neuronal excitability, intracellular Ca 21 increase, synaptic plasticity, and pain (Snyder et al, 2001;Ireland and Abraham, 2002;Gubellini et al, 2003;Rae and Irving, 2004). Homer proteins are known to link mGluRs to other postsynaptic density proteins (Shiraishi-Yamaguchi and Furuichi, 2007;Niswender and Conn, 2010) and play a vital role in coupling the receptors with downstream effectors (Mao et al, 2005;Jung et al, 2007;Won et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mGlu5 leads to a protein-translation-dependent increase in mediators involved in AMPA receptor endocytosis (Snyder et al, 2001;Bear et al, 2004). Since mGlu5-mediated protein synthesis was abolished by GluD1 deletion, we investigated whether mGlu5-mediated AMPA receptor internalization was also affected in GluD1 KO.…”
Section: Glud1 Regulates Mglu5 Signalingmentioning
confidence: 99%
“…Although this seems to be the case in mature neurons, NMDARs move rapidly into and out of synapses in developing neurons 15,18,34 . It is likely that synaptic removal of NMDARs involves a combination of lateral diffusion 15,34 and endocytosis [16][17][18] . Although the mechanisms have been unclear, this process is almost certainly determined by a balance between interactions with scaffolding proteins that anchor receptors at the PSD, and interactions with adaptors that target NMDARs to the endocytic machinery for membrane removal 25 .…”
Section: Nmdar Mobility and Receptor Endocytosismentioning
confidence: 99%
“…Substantial evidence also supports a role for exocytic and endocytic receptor cycling in controlling AMPAtype glutamate receptor abundance at synapses during synaptic plasticity, but NMDARs have conventionally been thought to be stably fixed within the postsynaptic density (PSD). Challenging this view, recent studies have revealed that NMDARs can move rapidly in and out of the neuronal surface [14][15][16][17][18][19][20] . Atleast some forms of NMDAR exocytic and endocytic trafficking require synaptic activity 21 or ligand binding 17,22 ,23 , and may initiate synaptic changes that lead to synapse stabilization or elimination during development 16,23 . Despite recent progress, our knowledge of how postsynaptic NMDARs are linked to and regulated by the endocytic machinery is only just emerging.…”
mentioning
confidence: 99%
“…The involvement of the mGluRs in hippocampal LTD has been well established (Bolshakov and Siegelbaum, 1994;Fitzjohn et al, 1999;O'Mara et al, 1995;Snyder et al, 2001), however their contribution to LTP has been a subject of unresolved debate (Bashir et al, 1993;Bortolotto et al, 1995;Chinestra et al, 1993;Manzoni et al, 1994;Richter-Levin et al, 1994;Riedel et al, 1995;Selig et al, 1995). To date, eight mGluR subtypes, designated mGluR1 to mGluR8, have been cloned from the mammalian brain.…”
Section: Introductionmentioning
confidence: 99%